2023
DOI: 10.12688/f1000research.122288.1
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence based glaucoma and diabetic retinopathy detection using MATLAB — retrained AlexNet convolutional neural network

Abstract: Background: Glaucoma and diabetic retinopathy are the leading causes of blindness due to an irreversible damage to the retina which results in vision loss. Early detection of these diseases through regular screening is especially important to prevent progression. The image of retinal fundus is the main evaluating strategy for the glaucoma and diabetic retinopathy detection. Then, automated eye disease detection is an important application of retinal image analysis. Compared with classical diagnostic techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The study [14] used a radial basis function neural network to detect DR with an accuracy of 89.4%. Using a retrained AlexNet CNN, the study [15] obtained 92.5% accuracy for DR diagnosis in another investigation.…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…The study [14] used a radial basis function neural network to detect DR with an accuracy of 89.4%. Using a retrained AlexNet CNN, the study [15] obtained 92.5% accuracy for DR diagnosis in another investigation.…”
Section: Related Workmentioning
confidence: 93%
“…Proposed Method Accuracy [15] AlexNet CNN 92.50% [13] KOA Based on BILSTM Network 84.09% [51] Deep learning-based method 90.60% [52] Hybrid deep learning 93.84% [53] Linear Model and Naïve Bayes 75.13% [54] Ensemble learning method 89.50% [55] SVM and DL 84.60% [56] Neural network 90.00% [22] RetNet-10 method 98.65% [23] DR-CCTNet method 90.17% Proposed Model CNN(Proposed) 95.27%…”
Section: Namementioning
confidence: 99%
“…This acceleration is achieved by leveraging pre-implemented functions for preprocessing, training, validation, and testing. MATLAB holds considerable prevalence in medical research and is a robust tool, as demonstrated by its application in recent drug-related studies leading to FDA approval [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consecutively [33], different databases of more than two diseases were used and gave acceptable validation ACC for the training process. This process was checked by five different versions of the AlexNet CNN (Net transfer I, Net transfer II, Net transfer III, Net transfer IV, and Net transfer V): 94.30%, 91.8%, 89.7%, 93.1%, and 92.10% successively [34]. Sharif A. Kamran presented the generative adversarial network (VTGAN).…”
Section: Related Workmentioning
confidence: 99%